2017
DOI: 10.1177/1533034617736162
|View full text |Cite
|
Sign up to set email alerts
|

DNA Repair Mechanism Gene, XRCC1A (Arg194Trp) but not XRCC3 (Thr241Met) Polymorphism Increased the Risk of Breast Cancer in Premenopausal Females: A Case–Control Study in Northeastern Region of India

Abstract: X-ray repair cross complementary group gene is one of the most studied candidate gene involved in different types of cancers. Studies have shown that X-ray repair cross complementary genes are significantly associated with increased risk of breast cancer in females. Moreover, studies have revealed that X-ray repair cross complementary gene polymorphism significantly varies between and within different ethnic groups globally. The present case–control study was aimed to investigate the association of X-ray repai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 85 publications
(113 reference statements)
0
3
0
Order By: Relevance
“…A previous study from the north-eastern region of India has reported no association of this polymorphism with breast cancer. 90 From Indian subcontinent, two populations practicing consanguineous marriages reported an association with increased risk, for colorectal cancer in Kashmiri population 50 and breast cancer in Pakistani population. 91 For XRCC3 p.Thr241Met polymorphism, no association was reported with gastric cancer in Italian population 92 and with colorectal cancer in the West Algerian population 93 but an association with an increased risk was reported for lung cancer in an Italian population, 23 oral SCC in Thai population, 94 and gastric cancer in the Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study from the north-eastern region of India has reported no association of this polymorphism with breast cancer. 90 From Indian subcontinent, two populations practicing consanguineous marriages reported an association with increased risk, for colorectal cancer in Kashmiri population 50 and breast cancer in Pakistani population. 91 For XRCC3 p.Thr241Met polymorphism, no association was reported with gastric cancer in Italian population 92 and with colorectal cancer in the West Algerian population 93 but an association with an increased risk was reported for lung cancer in an Italian population, 23 oral SCC in Thai population, 94 and gastric cancer in the Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study by Santos et al [39] additionally observed that the XRCC3 Thr241Met variant was slightly associated with an increased risk of BC in individuals with elevated chromosomal damage. However, reports from certain ethnicities have observed a lack of association between XRCC3 Thr241Met variant and BC risk [25,26,[40][41][42][43].…”
Section: Plos Onementioning
confidence: 98%
“…Similarly, association of XRCC2 and XRCC3 polymorphism with lung (12) and breast cancer (13) have been studied. However, findings from earlier studies continued with contradiction which failed to prove the association of SNPs in XRCC genes with risk of multiple cancers (14,15) . Number of studies demonstrated the pronounced susceptibility of gastric cancer in association with SNPs of XRCC genes (16,17) .…”
Section: Introductionmentioning
confidence: 96%